Clusters and Territorial-Industrial Complexes - Similar Approaches or Different Concepts? - first Evidence from Analysis of Development of Russian Regions - Igor Pilipenko (European Regional Science Association (ERSA), 2005)
The cluster concept has been attracting a special attention of scholars and policymakers since almost 15 years due to considerable contribution of its theoretical results to practical rising of national and regional competitiveness. The concept of territorial-industrial complex (TIC) elaborated by Soviet regional economists and economic geographers in 1920-1980s realised the idea of optimisation of industrial production within a certain territory in the planning economy according to its endowments of natural and labour resources. At the first sight, these two concepts have many things in common, but in reality they have many differences. First, they were elaborated in different economic systems, which have various aims of economic activity. Secondly, clusters and TICs have different genesis, because in case of TICs theoretical and applied research resulted in practical construction of TICs, while clusters are generally forming themselves as a result of the market "invisible hand”. Thirdly, clusters and TICs are normally located in different types of regions: clusters tend to form in within agglomerations, while TICs were constructed mainly in newly developed regions with low population density. Fourthly, they differ also in terms of their structure. Clusters are groups of companies from one or related in industries often connected to R&D institutions and government structures, but TICs are inter-industrial complexes that involve production chains between different industries. Fifthly, cluster firms specialise in production of buyer-oriented good and services, while TICs' plants and factories represented producer-oriented heavy industries and machinery. Sixthly, the role of information flows between cluster SMEs and their staffs makes one of key distinctions between these two concepts. Seventhly, higher wages in cluster labour pools and higher productivity in cluster firms lead to raising of regional competitiveness while in the concept of TICs people are considered to be one of factors of TIC's development as well as natural resources, infrastructure, etc. A general weak development of SMEs in Russia restricts so far the development of regional/local clusters, but nevertheless some examples of local clusters can be found. One of them is an expanding cluster of small and medium IT-enterprises in Novosibirsk (Western Siberia) that has been developing since the beginning of 1990s in the region that inherits its original industrial specialization from TICs. The cluster firms have tight connections to R&D institutions from Akademgorodok (Science city), Novosibirsk State University, and Technopark Novosibirsk; the intensive information flows and exchange of know-how can be observed between cluster firms and their staffs; the productivity and wages within cluster are higher than in surrounding districts. Development of clusters of SMEs makes differences between clusters and TICs more obvious. The further development of Russian economy may lead to its dual spatial structure – combination of big and medium plants established within TIC concept till the end of 1980s and clusters of SMEs developing since the beginning of 1990s in agglomerations.
Keywords: 330